Silver Nanoparticles Induce a Triclosan-Like Antibacterial Action Mechanism in Multi-Drug Resistant Klebsiella pneumoniae - Pareek, Vikram; Devineau, Stéphanie; Sivasankaran, Sathesh K.; Bhargava, Arpit; Panwar, Jitendra; Srikumar, Shabarinath; Fanning, Séamus (Frontiers in Microbiology, 2021)
Infections associated with antimicrobial-resistant bacteria now represent a significant threat to human health using conventional therapy, necessitating the development of alternate and more effective antibacterial compounds. Silver nanoparticles (Ag NPs) have been proposed as potential antimicrobial agents to combat infections. A complete understanding of their antimicrobial activity is required before these molecules can be used in therapy. Lysozyme coated Ag NPs were synthesized and characterized by TEM-EDS, XRD, UV-vis, FTIR spectroscopy, zeta potential and oxidative potential assay. Biochemical assays and deep level transcriptional analysis using RNA sequencing were used to decipher how Ag NPs exert their antibacterial action against multi-drug resistant Klebsiella pneumoniae MGH78578. RNAseq data revealed that Ag NPs induced a triclosan-like bactericidal mechanism responsible for the inhibition of the type II fatty acid biosynthesis. Additionally, released Ag+ generated oxidative stress both extra- and intracellularly in K. pneumoniae. The data showed that triclosan-like activity and oxidative stress cumulatively underpinned the antibacterial activity of Ag NPs. This result was confirmed by the analysis of the bactericidal effect of Ag NPs against the isogenic K. pneumoniae MGH78578 ΔsoxS mutant, which exhibits a compromised oxidative stress response compared to the wild type. Silver nanoparticles induce a triclosan-like antibacterial action mechanism in multi-drug resistant K. pneumoniae. This study extends our understanding of anti-Klebsiella mechanisms associated with exposure to Ag NPs. This allowed us to model how bacteria might develop resistance against silver nanoparticles, should the latter be used in therapy.